Acupuncture in the treatment of finger pulley Injury: a quantitative study - Zhao, Chenxi (Nanyang Technological University, 2023)
With the growth in popularity of rock climbing as a sport, finger pulley injuries have become an increasingly prevalent problem. This study aims to investigate the prevalence of finger pulley injuries amongst climbers in Singapore through a survey of 109 participants, as well as the effectiveness of acupuncture performed on the A2, A3 or A4 pulleys on functional finger strength recovery through a pilot clinical trial of 19 participants.